Ethical Leadership and Decision Making in Education : applying theoretical perspectives to complex dilemmas - Shapiro, Joan Poliner; Stefkovich, Jacqueline Anne, 1947- (New York, NY : Routledge, 2022)
"The fifth edition of the best-selling text, Ethical Leadership and Decision Making in Education, continues to address the increasing interest in ethics and assists educational leaders with complex dilemmas in today's challenging, divided, and diverse societies. Through discussion and analysis, Shapiro and Stefkovich demonstrate the application of four ethical paradigms - the ethics of justice, critique, care, and the profession. After illustrating how the Multiple Ethical Paradigms may be applied to authentic dilemmas, the authors present cases written by graduate students, practitioners, and academics representing dilemmas faced by educational leaders in urban, suburban, and rural public and private schools and universities, in the U.S. and abroad. Following each case are questions that call for thoughtful, complex thinking and help readers apply the Multiple Ethical Paradigms to practical situations. New in the Fifth Edition are more than ten new cases that cover issues of food insufficiency, the pandemic's effects on diverse school populations, a student's sexual orientation, transgender students in the university, lock-down drills for young children, refugees in a Swedish school, boundaries in high school sports, generational differences in an adult diploma school, acceptance of animals on campus, and hate speech in the academy. This edition also includes teaching notes for the instructor stressing the importance of self-reflection, use of new technologies, and global appeal of ethical paradigms and dilemmas. This book is a critical resource for aspiring and practicing administrators, teacher leaders, and educational policy makers"--
Includes bibliographical references and index.
Keywords: Educational leadership -- Moral and ethical aspects -- United States; School administrators -- Professional ethics -- United States; School management and organization -- Moral and ethical aspects -- United States; Ethics -- Study and teaching -- United States; Decision making -- United States